CONTENT OF BOWMAN-BIRK INHIBITOR IN SEEDS OF SOYBEAN VARIETIES OF ODESA SELECTION - V. Malinovskii; V. Sichkar; А. Levytskyi; А. Lapinska (Zernovì Produkti ì Kombìkorma, 2024)
The article shows that proteolysis (enzymatic hydrolysis of proteins) is a fundamental biological reaction that underlies such biological processes as digestion, reutilization of tissue proteins, immunity, neuroendocrine regulation, inflammation and dystrophy, and in some cases, as defense against pathogens. The most important regulators of proteolysis are inhibitors of proteolytic enzymes, which make them effective factors influencing the state of a significant number of biological processes. There are 2 inhibitors of proteolytic enzymes in soybeans: Kunitz inhibitor (KI), which inhibits trypsin, and Bowman-Birk inhibitor (BBI), which inhibits trypsin, chymotrypsin, elastase, cathepsins, and microbial proteases. Unlike the KI inhibitor, the BBI inhibitor is thermostable and remains in soy products (meal, cake) after defatting. Therefore, it is important to use soy products with a minimum content of BBI in feeding animals. Goal of work. To determine the content of BBI in promising soybean varieties of Odesa selection. Materials and methods. 12 soybean varieties of the Odesa selection were studied (Euridika, Orpheus, Aurora, Pivdenna zorya, Ariadna, Phoenix, Vasylkivska, Taverna, Serenada, Odesitka, Zmina, Zvytyaga). After grinding the beans and defatting the flour with acetone, the inhibitor was extracted with acetate buffer (0.05 M, pH 4.5) and the extract was mixed with three volumes of acetone. After keeping the mixture at a temperature of -16°C for 2 days, the precipitate was centrifuged and dissolved in 0.5% NaHCO3. The content of BBI was determined by the effect on chymotrypsin, the activity of which was assessed by the rate of casein hydrolysis by Kunitz-Levytskyi method. Results. It was established that the content of BBI in the investigated soybean varieties varies from 93.6 ?g/g (Euridika) to 368.8 ?g/g (Serenada). The soybean varieties Taverna (323.8 ?g/g), Vasylkivska (290.9 ?g/g), as well as Zmina (282.0 ?g/g) and Ariadna (263.0 ?g/g) are characterized by a high content of BBI. Conclusion. New soybean varieties of the Odesa selection contain a small amount of BBI and can be used in animal feeding after conventional heat treatment without additional BBI removal.